TATA KOTA PAREPARE PERIODE KOLONIAL BELANDA - Muhajir Muhajir; Muhammad Nur (Balai Arkeologi Provinsi Sulawesi Selatan, 2019)
The focus of this research is the port city of Parepare in the Dutch Colonial period. The problem posed is how the form of urban planning and the factors that influence the form of the city of Parepare in the Dutch Colonial period. The method used is the determination of the dimensions of Colonial buildings based on inscriptions, texts and interviews. Mapping of building layout and road network as well as analysis of building functions, urban space organizations, and analysis of the factors forming city spatial planning are also carried out. The results of the study indicate that the city planning of Parepare consists of three zones. The first zone is the core of the city occupied by the Dutch government as the center of government. The second zone is the Chinatown area, intended for economic activities. The third zone is for indigenous settlements. The shape of the city extends from north to south following the coastline. The road network in the city center has a grid pattern. The dominant factor affecting the shape of the city of Parepare is geopolitical and security factors, to maintain the conduciveness of the western coastal region of South Sulawesi.Fokus penelitian ini adalah Kota pelabuhan Parepare pada periode Kolonial Belanda. Permasalahan yang diajukan adalah bagaimana bentuk tata kota dan faktor-faktor yang mempengaruhi bentuk tata kota Parepare pada periode Kolonial Belanda. Metode yang digunakan adalah penentuan dimensi bangunan Kolonial berdasarkan prasasti, naskah dan hasil wawancara. Pemetaan tata letak bangunan dan jaringan jalan serta analisis fungsi bangunan, organisasi ruang kota, dan analisis faktor pembentuk tata ruang kota juga dilakukan. Hasil penelitian menunjukkan bahwa tata kota Parepare terdiri dari tiga zona. Zona pertama merupakan inti kota ditempati oleh pemerintah Belanda sebagai pusat pemerintahan. Zona kedua adalah kawasan pecinan, diperuntukkan untuk kegiatan perekonomian. Zona ketiga diperuntukkan untuk pemukiman pribumi. Bentuk kota memanjang dari utara ke selatan mengikuti garis pantai. Jaringan jalan pada pusat kota berpola grid. Faktor yang dominan mempengaruhi bentuk kota Parepare adalah faktor geo-politik dan keamanan, untuk menjaga kondusifnya wilayah pesisir barat Sulawesi Selatan.